Nanocrystalline magnetically soft alloy and preparation method thereof

By adding an appropriate amount of Ni, Mo and P elements to the nanocrystalline soft magnetic alloy to control its content ratio, the problem of fast saturation speed and reduced effective magnetic permeability under the DC magnetic field is solved, and a higher anti-DC capability and inductance retention rate are achieved.

CN119506723APending Publication Date: 2025-02-25ZHEJIANG BOTU MAGNETIC INTELLIGENT MANUFACTURING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411683330.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing nanocrystalline soft magnetic alloys have fast saturation speed under the magnetic field with DC components, and the effective magnetic permeability decreases at a large speed and amplitude, resulting in increased core loss and local overheating.

Method used

By adding Ni, Mo and P elements to the alloy system to control their content ratio, Ni reduces the initial relative magnetic permeability and AC loss, Mo significantly reduces the initial relative magnetic permeability and slows down its rate of change with the external field, P refines the grain size and reduces the magnetocrystal anisotropy, thereby improving the anti-DC capability.

Benefits of technology

It significantly reduces the saturation rate of nanocrystalline soft magnetic alloy under the DC magnetic field, slows down the speed and amplitude of effective magnetic permeability, reduces the risk of core loss and local overheating, and improves the inductance retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148896330000081
    Figure BDA0005148896330000081
  • Figure BDA0005148896330000091
    Figure BDA0005148896330000091
Patent Text Reader

Abstract

The invention relates to the technical field of magnetic materials, and particularly discloses a nanocrystalline soft magnetic alloy and a preparation method thereof. The molecular formula of the nanocrystalline soft magnetic alloy is Fe < 77-x > Ni < x > Si < 11.5-y > PyB < 8 > Nb < 2.7-z > Mo < z > Cu < 0.8 >, x is equal to 6-15, y is equal to 2-4, and z is equal to 1-2.5; the preparation method comprises the following steps: S1, preparing a strip-shaped amorphous alloy; and S2, the strip-shaped amorphous alloy is subjected to copper coating treatment, then the temperature is increased to 480-550 DEG C according to the temperature increasing rate of 20-25 DEG C / min, heat treatment is conducted for 10-30 min at the temperature, finally air cooling is conducted to the room temperature, the nanocrystalline soft magnetic material is obtained, and in the copper coating treatment, the thickness ratio of a copper metal layer to the strip-shaped amorphous alloy is (1-2): 1. The product provided by the invention can be used for a magnetic field with a direct current component, and has the characteristics of high direct current resistance and excellent soft magnetic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnetic materials, and in particular to a nanocrystalline soft magnetic alloy and a preparation method thereof. Background Art

[0002] Nanocrystalline soft magnetic alloy refers to a soft magnetic alloy with a nanocrystalline structure obtained by heat treatment on the basis of an amorphous alloy. It is mainly composed of Fe-based alloys and usually contains elements such as Si, B, Cu, and Nb. This material is prepared by processes such as rapid solidification or mechanical alloying to form a nanocrystalline structure with high-density grain boundaries, showing excellent soft magnetic properties, specifically high saturation magnetic induction intensity, low coercive force, low magnetic loss, good temperature stability and processability, so that it can reach saturation magnetization at a lower magnetic field intensity, and the demagnetization process is also very simple. It can effectively suppress eddy current and hysteresis losses, and can still maintain a good working state in an environment with high temperature or large temperature fluctuations. It can be processed into various shapes by shearing, stamping and other methods. The above advantages make nanocrystalline soft magnetic alloys widely used in power electronics, communications, automotive electronics, aerospace and other fields, especially in high-frequency and high-efficiency electromagnetic equipment.

[0003] In the field of power electronics, nanocrystalline soft magnetic alloys are widely used in electronic devices such as filters, transformers, precision current transformers, high-frequency transformers, and common-mode inductors. The tricky thing is that there are DC components in the working environment of these devices, which will cause the nanocrystalline soft magnetic alloys to quickly saturate under the magnetic field. At this time, the effective magnetic permeability will drop rapidly. At the same time, the DC component will cause the core loss to increase and the equipment to overheat locally. Therefore, some researchers have proposed that the DC resistance of nanocrystalline soft magnetic alloys can be improved by doping with Co elements, but the large-scale use of Co will greatly increase the production cost of the alloy and is not suitable for industrial production. Therefore, how to solve the problem of poor DC resistance of existing nanocrystalline soft magnetic alloys has become a current priority. Summary of the invention

[0004] In order to solve the above technical problems, the present application provides a nanocrystalline soft magnetic alloy and a preparation method thereof.

[0005] In a first aspect, the present application provides a nanocrystalline soft magnetic alloy, wherein the molecular formula of the nanocrystalline soft magnetic alloy is Fe 77-x Ni x Si 11.5-y P y B8 2.7-z Mo z Cu 0.8 , where x=6-15, y=2-4, z=1-2.5.

[0006] Preferably, in the molecular formula, x=9-11.

[0007] Preferably, in the molecular formula, x=10.5.

[0008] Preferably, in the molecular formula, y=3.5, z=2-2.5.

[0009] By adopting the above technical scheme, the present application adds Ni, Mo and P into the alloy system. Ni has a negative magnetostriction coefficient, which can effectively reduce the initial relative magnetic permeability of the alloy and reduce the AC loss of the alloy during use. Mo can more significantly reduce the initial relative magnetic permeability of the alloy and greatly reduce the rate at which the relative magnetic permeability of the alloy changes with the external field. P can refine the grain size inside the alloy, thereby reducing the magnetocrystalline anisotropy of the grains, thereby reducing the coercive force of the alloy. The three elements Ni, Mo and P cooperate with each other to jointly improve the DC resistance of the nanocrystalline soft magnetic alloy under the condition that the soft magnetic properties of the alloy are not affected. The saturation speed of the nanocrystalline soft magnetic alloy in a magnetic field with a DC component is greatly reduced, and the speed and amplitude of the decrease in effective magnetic permeability are also reduced. At the same time, the degree of core loss is reduced, and local overheating almost does not occur during use.

[0010] In addition, the present application strictly controls the contents of the three elements Ni, Mo and P in the alloy. The three elements balance each other. When the content is insufficient, they cannot play the role they should play. However, if the Ni content is too much, the magnetocrystalline anisotropy of the alloy will increase rapidly and the coercive force will increase; if the Mo content is too much, the grain size inside the alloy will increase rapidly and the coercive force will increase; if the P content is too large, the initial relative magnetic permeability of the alloy will increase sharply. Therefore, within the content range strictly controlled by the present application, the nanocrystalline soft magnetic alloy has a coercive force of less than 5.30A / m and a saturation magnetic induction intensity of more than 1.60T, and has excellent soft magnetic properties. More importantly, it also has an initial relative magnetic permeability of less than 6.99k, and has very excellent DC resistance. Under the conditions of an external field strength of 300A / m and an applied frequency of 10kHz, the inductance retention rate is not less than 80%.

[0011] Specifically, the present application first controls the content ratio of Ni and Fe, thereby increasing the inductance retention rate of the nanocrystalline soft magnetic alloy by more than 2.93%, and on this basis further strictly controls the content ratio of Mo, Nb and the content ratio of P, Si, thereby further increasing the inductance retention rate of the nanocrystalline soft magnetic alloy to more than 83.46%, and up to 87.16%, which has a very significant DC resistance.

[0012] In a second aspect, the present application provides a method for preparing a nanocrystalline soft magnetic alloy, comprising the following steps: S1. Mixing materials according to the molecular formula, smelting to obtain alloy ingots, and making the alloy ingots into strip-shaped amorphous alloys; S2. The strip-shaped amorphous alloy is subjected to copper coating treatment, and then the temperature is increased to 480-550°C at a heating rate of 20-25°C / min, and heat treatment is performed at this temperature for 10-30 minutes, and finally air-cooled to room temperature to obtain a nanocrystalline soft magnetic material. In the copper coating treatment, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy is (1-2):1.

[0013] By adopting the above-mentioned technical scheme, copper plating is utilized in the preparation method of the present application, which effectively improves the distribution of the internal temperature field of the strip-shaped amorphous alloy during heat treatment, reduces the temperature difference at different positions of the strip-shaped amorphous alloy during the insulation stage, promotes the uniformity of its internal stress distribution, shortens the annealing time, and thus improves the heat treatment efficiency. More importantly, the copper plating can promote the simultaneous crystallization of the inner and outer positions of the strip-shaped amorphous alloy, and the resulting nanocrystalline soft magnetic alloy has a small internal grain size fluctuation range, more stable magnetic energy during use, higher saturation magnetic induction intensity, lower initial relative magnetic permeability, DC loss and coercive force, which means that the copper plating makes the nanocrystalline soft magnetic alloy have both good soft magnetic properties and DC resistance.

[0014] Preferably, in S2, the temperature during heat treatment is 525-550°C and the time is 20-30 minutes.

[0015] Preferably, in S2, the temperature during heat treatment is 545-550°C and the time is 25 minutes.

[0016] By adopting the above technical solution, the present application strictly controls the temperature and time during heat treatment, so that the coercive force, relative magnetic permeability loss rate and saturation magnetic induction intensity of the nanocrystalline soft magnetic alloy are in balance.

[0017] Preferably, in S2, the thickness ratio of the copper metal layer in the copper plating process to the strip-shaped amorphous alloy is (1.5-2):1.

[0018] By adopting the above technical solution, the present application strictly controls the thickness ratio of the copper metal layer and the strip-shaped amorphous alloy in the copper coating process, so that the coercive force, relative magnetic permeability loss rate and saturation magnetic induction intensity of the nanocrystalline soft magnetic alloy are in balance, while further improving its DC resistance. Experimental data proves that its inductance retention rate can reach up to 85.54%.

[0019] In summary, this application has the following beneficial technical effects: 1. The present application adds Ni, Mo and P to the alloy system. The three elements cooperate with each other to jointly improve the DC resistance of the nanocrystalline soft magnetic alloy under the condition that the soft magnetic properties of the alloy are not affected. The saturation speed in the presence of a DC component magnetic field is greatly reduced, and the decrease speed and amplitude of the effective magnetic permeability are also reduced. It has a coercive force of less than 5.30A / m, a saturation magnetic induction intensity of more than 1.60T and an initial relative magnetic permeability of less than 6.99k. Under the conditions of an external field strength of 300A / m and an applied frequency of 10kHz, its inductance retention rate is not less than 80%, and the core loss is reduced, and local overheating is almost non-existent during use. 2. The preparation method of the present application utilizes copper plating, which effectively improves the distribution of the internal temperature field of the strip-shaped amorphous alloy during heat treatment, reduces the temperature difference at different positions of the strip-shaped amorphous alloy during the insulation stage, promotes the uniform distribution of its internal stress, shortens the annealing time, and thus improves the heat treatment efficiency. More importantly, the copper plating can promote the simultaneous crystallization of the inner and outer positions of the strip-shaped amorphous alloy, and the resulting nanocrystalline soft magnetic alloy has a small internal grain size fluctuation range, more stable magnetic energy during use, and lower relative permeability loss rate and coercive force, which means that the copper plating makes the nanocrystalline soft magnetic alloy have both good soft magnetic properties and DC resistance; 3. The present application strictly controls the temperature and time during heat treatment and the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy in the copper coating treatment, so that the coercive force, relative magnetic permeability loss rate and saturation magnetic induction intensity of the nanocrystalline soft magnetic alloy are in balance. DETAILED DESCRIPTION

[0020] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Electrolytic iron was purchased from Tim (Beijing) New Material Technology Co., Ltd., with a content of 99.95wt%, a particle size of 2um, a hardness of 2HB, and a smoothness of 3.2; Nickel was purchased from Dongguan Ouyide Metal Materials Co., Ltd., with a content of 99.9wt%, standard mesh, and a compressive strength of 380MPa; Pure silicon was purchased from Suzhou Haichuan Rare Metal Products Co., Ltd., with a content of 99.99wt%; Ferroboron was purchased from Yumu New Materials Co., Ltd., with a content of 99.9wt% and an iron content of 72wt%; Ferrophosphorus was purchased from Zhengzhou Xingyan Mining Co., Ltd., with a content of 99.9wt%, a silicon content of 0.1-6wt%, an iron content of 30wt%, and a phosphorus content of 15-20wt%; Niobium was purchased from Nangong Xindun Alloy Welding Material Spraying Co., Ltd., with a content of 99.95wt%; Molybdenum was purchased from Baoji Magotan Nonferrous Metal Materials Co., Ltd., with a content of 99.95wt%; Electrolytic copper was purchased from Zhengzhou Xingyan Mining Co., Ltd., with a content of 99.97wt% and a resistivity of ≤0.0177Ωmm / mm 2 , hardness ≥65HB, electroplating grade, density 8.95g / cm 3 .

[0021] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0022] Example 1.1 A method for preparing a nanocrystalline soft magnetic alloy comprises the following steps: S11, according to the molecular formula Fe 71 Ni6Si 7.5 P4B8 1.7 Mo1Cu 0.8 The ingredients are prepared and put into a boron nitride crucible. The inside of the furnace body and the cooling copper mold are cleaned with ethanol. The boron nitride crucible is placed in the induction coil, the furnace door is closed after the position is adjusted, and the mechanical pump is turned on. After the vacuum degree in the furnace is as low as 10Pa, the diffusion pump is turned on. When the vacuum degree in the furnace drops to 5×10-3Pa, the diffusion pump is turned off, argon gas is flushed into the furnace, and the gas washing operation is repeated twice. Then the coil current is adjusted to 250A, preheated for 6min, and smelting is started. After the smelting is completed, the heat is kept for 5min, and then the current is disconnected. The liquid alloy melt is poured into the cooling copper mold, completely cooled to room temperature, and then the air valve is opened to balance the pressure in the system, and finally the alloy ingot is taken out; S12, placing the alloy ingot into a glass quartz tube with a nozzle slit at the lower end, heating the alloy ingot in the quartz tube by using an induction coil until it is completely melted, filling the quartz tube with high-pressure argon gas, spraying the liquid alloy melt onto a high-speed rotating copper roller, and using the rotating copper roller to quickly cool the melt to form an amorphous strip, thereby obtaining a strip-shaped amorphous alloy with a thickness of 22 um; S2. The strip-shaped amorphous alloy is copper-clad, with the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy being 1:1. The temperature is raised to 480°C at a heating rate of 20°C / min, and heat treatment is performed at this temperature for 30 minutes. Finally, the nanocrystalline soft magnetic material is air-cooled to room temperature.

[0023] Example 1.2 A method for preparing a nanocrystalline soft magnetic alloy comprises the following steps: S11, according to the molecular formula Fe 62 Ni 15 Si 9.5 P2B8 0.2 Mo 2.5 Cu 0.8The ingredients are prepared and put into a boron nitride crucible. The inside of the furnace body and the cooling copper mold are cleaned with ethanol. The boron nitride crucible is placed in the induction coil, the furnace door is closed after the position is adjusted, and the mechanical pump is turned on. After the vacuum degree in the furnace is as low as 10Pa, the diffusion pump is turned on. When the vacuum degree in the furnace drops to 5×10-3Pa, the diffusion pump is turned off, argon gas is flushed into the furnace, and the gas washing operation is repeated twice. Then the coil current is adjusted to 250A, preheated for 6min, and smelting is started. After the smelting is completed, the heat is kept for 5min, and then the current is disconnected. The liquid alloy melt is poured into the cooling copper mold, completely cooled to room temperature, and then the air valve is opened to balance the pressure in the system, and finally the alloy ingot is taken out; S12, placing the alloy ingot into a glass quartz tube with a nozzle slit at the lower end, heating the alloy ingot in the quartz tube by using an induction coil until it is completely melted, filling the quartz tube with high-pressure argon gas, spraying the liquid alloy melt onto a high-speed rotating copper roller, and using the rotating copper roller to quickly cool the melt to form an amorphous strip, thereby obtaining a strip-shaped amorphous alloy with a thickness of 22 um; S2. The strip-shaped amorphous alloy is copper-clad, with the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy being 2:1. The temperature is raised to 550°C at a heating rate of 25°C / min, and a heat treatment is performed at this temperature for 10 minutes. Finally, the nanocrystalline soft magnetic material is air-cooled to room temperature.

[0024] Example 1.3 A method for preparing a nanocrystalline soft magnetic alloy comprises the following steps: S11, according to the molecular formula Fe 69 Ni8Si 8.5 P3B8 2.5 Mo 1.2 Cu 0.8 The ingredients are prepared and put into a boron nitride crucible. The inside of the furnace body and the cooling copper mold are cleaned with ethanol. The boron nitride crucible is placed in the induction coil, the furnace door is closed after the position is adjusted, and the mechanical pump is turned on. After the vacuum degree in the furnace is as low as 10Pa, the diffusion pump is turned on. When the vacuum degree in the furnace drops to 5×10-3Pa, the diffusion pump is turned off, argon gas is flushed into the furnace, and the gas washing operation is repeated twice. Then the coil current is adjusted to 250A, preheated for 6min, and smelting is started. After the smelting is completed, the heat is kept for 5min, and then the current is disconnected. The liquid alloy melt is poured into the cooling copper mold, completely cooled to room temperature, and then the air valve is opened to balance the pressure in the system, and finally the alloy ingot is taken out; S12, placing the alloy ingot into a glass quartz tube with a nozzle slit at the lower end, heating the alloy ingot in the quartz tube by using an induction coil until it is completely melted, filling the quartz tube with high-pressure argon gas, spraying the liquid alloy melt onto a high-speed rotating copper roller, and using the rotating copper roller to quickly cool the melt to form an amorphous strip, thereby obtaining a strip-shaped amorphous alloy with a thickness of 22 um; S2. The strip-shaped amorphous alloy is copper-clad, with the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy being 1.3:1. The temperature is raised to 510°C at a heating rate of 22.5°C / min, and heat treatment is performed at this temperature for 20 minutes. Finally, the nanocrystalline soft magnetic material is air-cooled to room temperature.

[0025] Example 2.1 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 1.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 68 Ni9Si 7.5 P4B8 1.7 Mo1Cu 0.8 , the rest are the same as in Example 1.1.

[0026] Example 2.2 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 1.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 67 Ni 10 Si 7.5 P4B8 1.7 Mo1Cu 0.8 , the rest are the same as in Example 1.1.

[0027] Example 2.3 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 1.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 66 Ni 11 Si 7.5 P4B8 1.7 Mo1Cu 0.8 , the rest are the same as in Example 1.1.

[0028] Example 2.4 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 2.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 67.5 Ni 9.5 Si 7.5 P4B8 1.7 Mo1Cu 0.8 , the rest are the same as Example 2.1.

[0029] Example 2.5 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 2.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 66.5 Ni 10.5 Si 7.5P4B8 1.7 Mo1Cu 0.8 , the rest are the same as Example 2.1.

[0030] Example 3.1 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 2.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 68 Ni9Si8P 3.5 B8 0.7 Mo2Cu 0.8 , the rest are the same as Example 2.1.

[0031] Example 3.2 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 2.1 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 68 Ni9Si8P 3.5 B8 0.2 Mo 2.5 Cu 0.8 , the rest are the same as Example 2.1.

[0032] Example 3.3 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 2.5 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 66.5 Ni 10.5 Si8P 3.5 B8 0.7 Mo2Cu 0.8 , the rest are the same as in Example 2.5.

[0033] Example 3.4 A method for preparing a nanocrystalline soft magnetic alloy, which is different from that of embodiment 2.5 in that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 66.5 Ni 10.5 Si8P 3.5 B8 0.2 Mo 2.5 Cu 0.8 , the rest are the same as in Example 2.5.

[0034] Example 4.1 A method for preparing a nanocrystalline soft magnetic alloy, which is different from Example 1.1 in that, in step S2, the temperature during heat treatment is 525° C., and the rest is the same as Example 1.1.

[0035] Example 4.2 A method for preparing a nanocrystalline soft magnetic alloy, which is different from Example 1.1 in that, in step S2, the temperature during heat treatment is 550° C. and the time is 20 min, and the rest is the same as Example 1.1.

[0036] Example 4.3 A method for preparing a nanocrystalline soft magnetic alloy, which is different from Example 1.1 in that, in step S2, the temperature during heat treatment is 537° C. and the time is 25 min, and the rest is the same as Example 1.1.

[0037] Example 5.1 A method for preparing a nanocrystalline soft magnetic alloy, which is different from Example 4.3 in that, in step S2, the temperature during heat treatment is 545°C, and the rest is the same as Example 4.3.

[0038] Example 5.2 A method for preparing a nanocrystalline soft magnetic alloy, which is different from Example 4.3 in that, in step S2, the temperature during heat treatment is 548°C, and the rest is the same as Example 4.3.

[0039] Example 5.3 A method for preparing a nanocrystalline soft magnetic alloy, which is different from Example 4.3 in that, in step S2, the temperature during heat treatment is 550°C, and the rest is the same as Example 4.3.

[0040] Example 6.1 A method for preparing a nanocrystalline soft magnetic alloy is different from that of Example 1.1 in that, in step S2, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy in the copper coating treatment is 1.5:1, and the rest is the same as that of Example 1.1.

[0041] Example 6.2 A method for preparing a nanocrystalline soft magnetic alloy is different from that of Example 1.1 in that, in step S2, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy in the copper coating treatment is 2:1, and the rest is the same as that of Example 1.1.

[0042] Example 6.3 A method for preparing a nanocrystalline soft magnetic alloy is different from that of Example 1.1 in that, in step S2, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy in the copper coating treatment is 1.8:1, and the rest is the same as that of Example 1.1.

[0043] Comparative Example 1.1 The difference from Example 1.1 is that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 77 Si 7.5 P4B8 1.7 Mo1Cu0.8 , the rest are the same as in Example 1.1.

[0044] Comparative Example 1.2 The difference from Example 1.1 is that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 68 Ni9Si 11.5 B8 1.7 Mo1Cu 0.8 , the rest are the same as in Example 1.1.

[0045] Comparative Example 1.3 The difference from Example 1.1 is that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 68 Ni9Si 7.5 P4B8 2.7 Cu 0.8 , the rest are the same as in Example 1.1.

[0046] Comparative Example 2.1 The difference from Example 1.1 is that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 57 Ni 20 Si 10. 5P1B8N 0.1 Mo 2.6 Cu 0.8 , the rest are the same as in Example 1.1.

[0047] Comparative Example 2.2 The difference from Example 1.1 is that in step S11, the molecular formula of the nanocrystalline soft magnetic alloy is Fe 72 Ni5Si 8.5 P5B8 2.2 Mo 0.5 Cu 0.8 , the rest are the same as in Example 1.1.

[0048] Comparative Example 3 The difference from Example 1.1 is that in step S2, copper plating is not performed, and the rest is the same as Example 1.1.

[0049] Comparative Example 4.1 The difference from Example 1.1 is that in step S2, in the copper coating process, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy is 3:1, and the rest is the same as Example 1.1.

[0050] Comparative Example 4.2 The difference from Example 1.1 is that in step S2, in the copper coating process, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy is 1:2, and the rest is the same as Example 1.1.

[0051] Comparative Example 5.1 The difference from Example 1.1 is that in step S2, the temperature of the heat treatment is 600°C, and the rest is the same as Example 1.1.

[0052] Comparative Example 5.2 The difference from Example 1.1 is that in step S2, the temperature of the heat treatment is 450°C, and the rest is the same as Example 1.1.

[0053] Performance Testing 1. The nanocrystalline soft magnetic alloys prepared in the examples and comparative examples were measured using a KEYSIGHT E4980A precision LCR meter. The test voltage was 1V, the frequency was 40-100kHz, and the accuracy was ±0.08%. The interval values ​​were logarithmically distributed using the built-in program of the instrument, and the initial relative permeability u i (k) recorded in Table 1; 2. The DC soft magnetic properties of the nanocrystalline soft magnetic alloys prepared in the examples and comparative examples were measured using a BHS-40 DC hysteresis loop instrument from Riken Denshi, including the saturation magnetic induction intensity B s (mT) and coercivity H c (A / m). Recorded in Table 1; 3. A copper enameled wire with a diameter of 1 mm was wound on the nanocrystalline soft magnetic alloy obtained in the embodiment and the comparative example. Under the conditions of an external field strength of 300 A / m and an applied frequency of 10 kHz, a DC resistance test was performed on the nanocrystalline soft magnetic alloy obtained in the embodiment and the comparative example. The inductance retention rate (%) is recorded in Table 1. The higher the inductance retention rate of the sample, the smaller the DC loss degree.

[0054] Table 1 Performance test table Data Analysis: As can be seen from Table 1, the initial relative magnetic permeability of Examples 1.1-1.3 of the present application is 6.90-6.93k, the saturation magnetic induction intensity is 1.61-1.62mT, the coercive force is 5.19-5.21A / m, and the inductance retention rate is 80.5-81.24% under the conditions of an external field intensity of 300A / m and an applied frequency of 10kHz. Both the initial relative magnetic permeability and the coercive force are low, and the saturation magnetic induction intensity is also at a high level, which proves that the present application adds Ni, Mo and P to the alloy system, and Ni has a negative magnetostriction coefficient, which can effectively reduce the initial relative magnetic permeability of the alloy, and can also reduce the AC loss of the alloy during use. Mo can significantly reduce the initial relative magnetic permeability of the alloy, and at the same time greatly reduce the rate at which the relative magnetic permeability of the alloy changes with the external field. P can refine the grain size inside the alloy, thereby reducing the magnetocrystalline anisotropy of the grains, thereby reducing the coercive force of the alloy. The three elements of Ni, Mo and P cooperate with each other to jointly improve the DC resistance of the nanocrystalline soft magnetic alloy under the condition that the soft magnetic properties of the alloy are not affected. The saturation speed of the nanocrystalline soft magnetic alloy in the presence of a DC component magnetic field is greatly reduced, and the speed and amplitude of the decrease in effective magnetic permeability are also reduced. At the same time, the degree of core loss is reduced, and local overheating almost does not occur during use. In Examples 2-3, the inductance retention rates are all greater than those in Example 1.1, proving that the present application has significantly improved its DC resistance as much as possible without affecting its soft magnetic ability by optimizing layer by layer and strictly controlling the proportion of each element in the nanocrystalline soft magnetic alloy; In Examples 4-6, the inductance retention rates are all greater than those in Example 1.1, proving that the present application has significantly improved its DC resistance as much as possible without affecting the soft magnetic ability of the nanocrystalline soft magnetic alloy by optimizing layer by layer and strictly controlling the process parameters in the heat treatment, so that the coercive force, relative magnetic permeability loss rate and saturation magnetic induction intensity of the nanocrystalline soft magnetic alloy are balanced and all have a high level; The inductance retention rate in comparative example 1 is much lower than that in embodiment 1.1, which proves that the present application makes full use of the three elements Ni, Mo and P to cooperate with each other, and jointly improves the DC resistance of the nanocrystalline soft magnetic alloy under the condition that the soft magnetic properties of the alloy are not affected. The saturation speed of the nanocrystalline soft magnetic alloy in the presence of a DC component magnetic field is greatly reduced, and the decline speed and amplitude of the effective magnetic permeability are also reduced. At the same time, the degree of core loss is reduced, and local overheating almost does not occur during use; the inductance retention rate in comparative example 2 is lower than that in embodiment 1.1, which proves that the present application strictly controls the content of the three elements Ni, Mo and P in the alloy, and the three elements check and balance each other. When the content is insufficient, they cannot play the effect they should play. However, if the Ni content is too much, the magnetocrystalline anisotropy of the alloy will rise rapidly and the coercive force will increase; if the Mo content is too much, the grain size inside the alloy will rapidly increase and the coercive force will increase; if the P content is too large, the initial relative magnetic permeability of the alloy will increase sharply; The inductance retention rate of comparative example 3 is lower than that of example 1.1, and the saturation magnetic induction intensity is lower than that of example 1.1, which proves that the copper coating treatment is used in the preparation method of the present application, which effectively improves the distribution of the internal temperature field of the strip-shaped amorphous alloy during heat treatment, reduces the temperature difference at different positions of the strip-shaped amorphous alloy during the insulation stage, promotes the uniformity of its internal stress distribution, shortens the annealing time, and thus improves the heat treatment efficiency. More importantly, the copper coating treatment can promote the simultaneous crystallization of the inner and outer positions of the strip-shaped amorphous alloy, and the internal grain size fluctuation range of the obtained nanocrystalline soft magnetic alloy is small, the magnetic energy in use is more stable, and it has a higher saturation magnetic induction intensity, a lower initial relative magnetic permeability, DC loss and coercive force, which means that the copper coating treatment makes the nanocrystalline soft magnetic alloy have both good soft magnetic properties and DC resistance. The inductance retention rate of comparative examples 4-5 is lower than that of embodiment 1.1, which proves that the present application has greatly improved its DC resistance as much as possible without affecting the soft magnetic ability of the nanocrystalline soft magnetic alloy by controlling the process parameters in the heat treatment, so that the coercive force, relative magnetic permeability loss rate and saturation magnetic induction intensity of the nanocrystalline soft magnetic alloy are in balance and all have a high level.

[0055] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A nanocrystalline soft magnetic alloy, characterized in that: The molecular formula of the nanocrystalline soft magnetic alloy is Fe 77-x Ni x Si 11.5- y P y B8 2.7-z Mo z Cu 0.8 , where x=6-15, y=2-4, z=1-2.

5.

2. A nanocrystalline soft magnetic alloy according to claim 1, characterized in that: In the molecular formula, x=9-11.

3. A nanocrystalline soft magnetic alloy according to claim 2, characterized in that: In the molecular formula, x=10.

5.

4. A nanocrystalline soft magnetic alloy according to claim 2 or 3, characterized in that: In the molecular formula, y=3.5, z=2-2.

5.

5. A method for preparing the nanocrystalline soft magnetic alloy according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Mixing materials according to the molecular formula, smelting to obtain alloy ingots, and making the alloy ingots into strip-shaped amorphous alloys; S2. The strip-shaped amorphous alloy is subjected to copper coating treatment, and then the temperature is increased to 480-550°C at a heating rate of 20-25°C / min, and heat treatment is performed at this temperature for 10-30 minutes, and finally air-cooled to room temperature to obtain a nanocrystalline soft magnetic material. In the copper coating treatment, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy is (1-2):

1.

6. The method for preparing the nanocrystalline soft magnetic alloy according to claim 5, characterized in that: In S2, the temperature during heat treatment is 525-550°C and the time is 20-30 minutes.

7. The method for preparing a nanocrystalline soft magnetic alloy according to claim 6, characterized in that: In S2, the temperature during heat treatment is 545-550°C and the time is 25 minutes.

8. The method for preparing a nanocrystalline soft magnetic alloy according to claim 5, characterized in that: In S2, the thickness ratio of the copper metal layer to the strip-shaped amorphous alloy in the copper plating process is (1.5-2):1.